Effet des endophytes fongiques sur la croissance des plants de concombre. - CHAMOUMA, FATIMA EL ZAHRA; BELAIDOUNI, ZOULIKHA MOUNA (My University, 2023)
In this study, the aim is to evaluate the effect of four mycoendophytic species on the growth of Cucumis sativus cucumber plants, three of them belong to the genera: Aspergillus, Torula and Alternaria. The results of the PGPF (Plant Growth Promoter Fungi) tests showed that most exhibited a strong zinc solubilization capacity, but neither produced hydrocyanic acid HCN nor inhibited the growth of the phytopathogene tested. The greenhouse growth of two-month-old cucumber plants inoculated with the four fungal species as well as their chlorophyll content are significantly better than controls (non-inoculated). The colonization of roots by fungal endophytes has been proven; therefore these endophytic fungi could be used in agriculture as biofertilizers to promote the growth of cucumber plants.
Keywords: Endophytic fungi; Cucumis sativus; PGPF; Biofertilizer